Risk Management Analysis on the Development Project for the Expansion of the Main Clinic Setara Handil Bakti Phase I, Alalak District, Barito Kuala Regency - Ery Foniati; Mursadin, Aqli (Technium: Romanian Journal of Applied Sciences and Technology, 2025)
In the implementation of construction project development, often experiencing various obstacles arising from the risks that occur where it results in the failure to achieve maximum performance, quality and achievement of work results as expected. The purpose of this study is to analyze the dominant risk factors that occur during the implementation of work in the field and to analyze risk management strategies in construction projects. In this study, risk identification, risk factor analysis and risk management strategies were carried out on the Setara Main Clinic Expansion Construction Work located in Handil Bakti, Barito Kuala Regency. The research method used was by means of a survey distributing indicator and risk factor questionnaires to construction supervisor/management consultants, contractors and related agencies. The ranking assessment of the risk indicator and risk factor questionnaires used the AS/NZS 4360 analysis. The results of the study showed 5 (five) dominant risks that occurred from sources of material, construction, environment effect and financial risks. The strategy in dealing with these dominant risks is by monitoring and managing the stages of workers and coordinating with the vendors involved and the related owners.